Numerical investigation of production performance of challenging gas hydrates from deposits with artificial fractures and impermeable barriers - Shuaishuai Nie; Ke Liu; Xiuping Zhong; Yafei Wang; Yalu Han; Kangtai Xu; Jian Song; Jiangfei Li (Scientific Reports)
Abstract In this research, a novel reservoir stimulation scheme combining impermeable artificial barriers and high-conductivity artificial fractures was introduced for gas hydrate extraction from clayey silt deposits, and the injection-production performance was numerically investigated using hydrates at the Shenhu SH2 site as the typical case scenario. The results indicated that impermeable barriers effectively addressed the challenges including boundary water intrusion, decomposition gas leakage, and injected hot fluid loss. Especially, artificial barriers and fractures exert a synergistic stimulation effect of “1 + 1 > 2”. The average gas production rate increased logarithmically as fracture conductivity increased, whereas the gas-to-water ratio and energy ratio, presented an opposite trend. The impact of injection pressure and production pressure on productivity was limited relative to hot water temperature, whereas low-temperature and low-pressure injection were more conducive to water control and energy utilization. Furthermore, parameter optimization based on multivariate nonlinear models suggested that commercial productivity and the Class II development standard for offshore gas reservoirs were expected to be achieved. Therefore, the combination of artificial fractures and impermeable boundaries is promising for clayey silt hydrate reservoir stimulation, offering a viable development mode for marine challenging hydrate.